2018
DOI: 10.1371/journal.pone.0201462
|View full text |Cite
|
Sign up to set email alerts
|

Detection of new pathways involved in the acceptance and the utilisation of a plant-based diet in isogenic lines of rainbow trout fry

Abstract: To meet the growing demand of fish feed for aquaculture, an increasing proportion of marine ingredients are being replaced by blends of plant products. However, the total replacement of marine ingredients in salmonid diets impairs fish performance. This is particularly true during the early fry stage and this stage is therefore considered of particular importance. In rainbow trout (RBT), the existence of a genetic variability to survive and grow with plant-based diets devoid of marine ingredients has now been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…Serotonin has also been shown to influence both lipid and glucose metabolism directly by suppressing lipolysis and glucose uptake in primary adipose cells ( Hansson et al, 2016 ). Specifically, the serotonin 1E receptor gene ( htr1e ) has been linked with feed intake in rainbow trout ( Callet et al, 2018 ) and in rats ( Hayes and Covasa, 2006 ). A recent study in pigs reported that intramuscular adipocytes showed dose-dependent serotonin stimulation, which then resulted in decreased fat accumulation in mature adipocytes ( Tada et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Serotonin has also been shown to influence both lipid and glucose metabolism directly by suppressing lipolysis and glucose uptake in primary adipose cells ( Hansson et al, 2016 ). Specifically, the serotonin 1E receptor gene ( htr1e ) has been linked with feed intake in rainbow trout ( Callet et al, 2018 ) and in rats ( Hayes and Covasa, 2006 ). A recent study in pigs reported that intramuscular adipocytes showed dose-dependent serotonin stimulation, which then resulted in decreased fat accumulation in mature adipocytes ( Tada et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The originality of this work rests on the use of the three isogenic lines of RBT as fish share the same genotype within each line, probably reducing variability in gene expressions within each isogenic line. As in the short-term study by Callet et al (2018), these specific features enhanced the capacity to detect differences between genotypes. Moreover, substitution of FM by plant ingredients in salmonids is known to affect fish feed intake (Gomes et al, 1995;Espe et al, 2006;Dupont-Nivet et al, 2009).…”
Section: Discussionmentioning
confidence: 98%
“…Finally, a recent study found several potential markers linked to feed intake and sensory perception among three different RBT isogenic lines (Callet et al, 2018). This last result suggests that differences in diet acceptance could explain the important variability observed in survival and growth during the first weeks after the firstfeeding with plant-based diets (Callet et al, 2018). Ultimately, only a few studies have investigated this question and the mechanisms which would explain this genetic variability have yet to be identified.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Transcriptome analysis of rainbow trout fry detected new pathways related with acceptance and utilization of plant‐based diet and identified several molecular markers linked to the utilization of plant‐based diet (Callet et al . ). Intestinal and liver transcriptome of rainbow trout identified only a low proportion of difference in metabolism related gene expression by the replacement of fishmeal and fish oils with a plant‐based diet (Lazzarotto et al .…”
Section: Current Status Of Transcriptomics In Aquaculturementioning
confidence: 97%